Why does China’s ICT (hardware and handset) industry has higher competitiveness than its Automotive? - chen, xiaoheng (Journal of Innovative Studies, 2020)
China has been know as the world’s factory in the past decades. Its GDP became the second biggest after USA, and export contributed nearly 35% to the GDP growth(Li,2013). But “Made in China” was regarded as cheap price with bad quality, since most of its export products were low value-added. As the global economy slowed down these years, this export-oriented economy would also be affected, and that is why China tried to develop high-tech industry to improve its international competitiveness,to transform its economic structure. ICT industry, specifically its hardware and handset, has achieved some international competitiveness. And this essay will compare Chinese ICT industry with its Automotive industry in terms of global competitiveness, and explain why ICT did better than Auto sector, which may give an inspiration about Chinese future high-tech development. (“ICT”, used in the essay, is all about ICT hardware and handset.)